Discovery of a phylogenetically novel tropical marine Gammaproteobacteria elucidated from assembled genomes and the proposed transfer of the genus Umboniibacter from the family Cellvibrionaceae to Umboniibacteraceae fam. nov. - Ho, Jia Yee; Koh, Xiu Qi; Kang, Deborah Yebon; Low, Adrian; Hu, Dalong; Haryono, Mindia A. S.; Williams, Rohan B. H.; Case, Rebecca J.; Boucher, Yann Felix (Frontiers in Microbiology, 2025)
Marine heterotrophic bacteria in coastal waters respond to the influx of carbon from natural and anthropogenic sources. We identified two nearly identical, (99.9% average nucleotide identity; 100% amino acid identity; same DNA G + C content of 52.3 mol%) high-quality (≥99% CheckM completeness and ≤ 1.3% contamination) draft metagenome-assembled genomes (MAGs; SJ0813 and SJ0972) from seawater microbiomes of a southern island of Singapore that is in a protected marine park. The MAGs were only assigned to the Cellvibrionaceae family according to Genome Taxonomy Database. Overall genome related indices to Pseudomaricurvus alkylphenolicus KU41GT as the closest phylogenetic relative revealed no more than 70.45% average nucleotide identity (ANIcutoff < 95%), below the 50% percentage of conserved proteins (POCPcutoff = 43.54%) for genera cutoff and low digital DNA–DNA hybridization values (DDH = 20.6 and 20.8%). The major respiratory quinone is predicted to be ubiquinone-9 from the annotation of 3-demethylubiquinone-9 3-methyltransferase (ubiG, K00568) involved in the last step of the ubiquinone biosynthesis pathway (M00117), which differed from the ubiquinone-8 utilized by known members of Cellvibrionaceae. Both MAGs contained a complete pathway for dissimilatory nitrate reduction to ammonia, which increases bioavailability of nitrogen in seawater. An identical choline dehydrogenase found in both MAGs have a low amino-acid identity (≤64.47%) compared to existing GMC family oxidoreductases, expanding on the diversity of this family of enzymes. The MAGs meet nearly all the minimum requirements but lack a 16S rRNA gene of sufficient length required for the proposed novel genus and species under SeqCode. Nevertheless, phylogenetic trees based on core-genome and RpoB as an alternative phylogenetic marker are congruent with the taxon standing as a monophyletic clade to other taxa of the order Cellvibrionales. Taken together, the MAGs (SJ0813 and SJ0972) represent an uncultured, undescribed genus and species in which we tentatively propose the name Candidatus Pelagadaptatus aseana gen. nov., sp. nov. and strain SJ0813TS (=BAABNI000000000.1TS) as type sequence. Phylogenetic inference from core-genome and RpoB phylogenetic trees placed Umboniibacter marinipuniceus KMM 3891T outside Cellvibrionaceae. We, therefore, propose the transfer of the genus Umboniibacter from the family Cellvibrionaceae to a new family Umboniibacteraceae according to the International Code of Nomenclature of Prokaryotes.